Rape as a weapon in genocide and wars: Enquiring the problems of women’s witnessing rape - Yuyun Sri Wahyuni (Journal of Social Studies (JSS), 2020)
This paper seeks to better understand rape as a weapon in genocide and wars, the myriads contributing factors to creating ignorance to rape as a weapon in genocide, other forms of sexual violations, and circumstances that prevent women from witnessing rape acts of genocide violence. Drawing from the feminist perspectives of rape and women's sexual violence theorization, Derrida's accounts of truth and witness, and women as an improper mythic being-tainted witness, this paper shows that the current global gender inequality discrimination perpetuates the practice of rape as a weapon of genocide and wars as well as a repudiation for women's witnessing rape and sexual violations. As this situation of women rape survivors' desertions are not only happened in the Rwanda genocide and witnessing rapes for rape victims and survivors are equally challenging, this paper serves an alternative to support women's witnessing rapes and prevent rape the weapon of war to reoccur in the future. Further, Derrida's considerations on law should extend the notions of witnessing beyond the traditional European juridical tradition that excludes literature from legal exercise of witnessing as literature is regarded as mostly only fiction upbrings witnessing through literature as secret testimony is a useful interpretation on women's witnessing rape. Deciphering Derrida's description of witnessing through literature, this paper also recommends that women's writing literature can be an effective way for women to testify independently of the various gendered political disciplining gazes that hold them back from giving testimonies and then gain liberations.